A Cognitive Poetic Analysis of ‘La Figlia che Piange’ by T.S. Eliot - Kareem, Raed Dakhil (Al-Adab Journal, 2020)
This paper attempts to employ the Text World Theory (TWT) to the processing of a selected literary discourse from a cognitive poetic and a literary-critical points of view. The selected text is ‘La Figlia che Piange’ by T.S. Eliot. TWT is regarded as a more powerful and dynamic theory in accounting for cognitive processes that underlie the production and even the interpretation of the different forms of discourse. TWT allows readers, speakers, listeners and hearers to interfere and produce and also process all types of discourse, whether factual or fictional, by constructing ‘text-worlds’ (e.g. mental representations in mind). The paper hypothesizes that this theory is a useful means of exploring poetic texts which are thematically structured. The paper ends up with some concluding points.